ANALYSIS OF THE DEEP LEARNING APPROACH TO MATHEMATICAL PROBLEM-SOLVING SKILLS AMONG EIGHTH-GRADE STUDENTS - Dewi Riska; Dadang Rahman Munandar; Iyan Rosita Dewi Nur (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Mathematical problem-solving is a fundamental competency that should be fostered through mathematics instruction, as it enables students to interpret, analyze, and solve various problems systematically. Despite its importance, many students still encounter difficulties in selecting appropriate solution strategies and evaluating the accuracy of their solutions. This study aimed to examine the mathematical problem-solving skills of eighth-grade students following the implementation of the deep learning approach based on Polya's problem-solving framework. A descriptive qualitative design was employed, and the study was conducted at a junior high school in Karawang Regency, Indonesia, during the second semester of the 2025/2026 academic year. The participants consisted of 41 eighth-grade students. Data were collected through classroom observations, teacher interviews, documentation, and a mathematical problem-solving test. The findings revealed that the deep learning approach created an engaging learning environment that promoted students' active participation through discussion, collaboration, question-and-answer activities, and group presentations. The analysis further indicated that most students were able to understand the given problems, develop appropriate solution strategies, and implement the planned procedures correctly. However, some students continued to experience difficulties during the looking back stage because they rarely reflected on or verified both the solution process and the final results. Overall, the findings suggest that the deep learning approach provides meaningful, contextual, and reflective learning experiences that contribute to the development of students' mathematical problem-solving skills. Therefore, this approach has the potential to serve as an effective instructional alternative for strengthening mathematical problem-solving skills in mathematics education. Kemampuan pemecahan masalah matematis merupakan kompetensi penting yang perlu dikembangkan dalam pembelajaran matematika karena membekali siswa dengan kemampuan memahami, menganalisis, dan menyelesaikan berbagai permasalahan secara sistematis. Meskipun demikian, masih banyak siswa yang mengalami kesulitan dalam menentukan strategi penyelesaian yang tepat serta melakukan refleksi dan verifikasi terhadap hasil yang diperoleh. Penelitian ini bertujuan mendeskripsikan kemampuan pemecahan masalah matematis siswa kelas VIII melalui penerapan pendekatan pembelajaran mendalam yang mengacu pada tahapan pemecahan masalah menurut Polya. Penelitian ini menggunakan metode deskriptif kualitatif dan dilaksanakan di salah satu sekolah menengah pertama di Kabupaten Karawang pada semester genap tahun ajaran 2025/2026 dengan melibatkan 41 siswa kelas VIII sebagai subjek penelitian. Data dikumpulkan melalui observasi, wawancara dengan guru, dokumentasi, serta tes kemampuan pemecahan masalah matematis. Hasil penelitian menunjukkan bahwa penerapan pendekatan pembelajaran mendalam mampu menciptakan proses pembelajaran yang lebih interaktif sehingga mendorong siswa untuk berpartisipasi aktif melalui kegiatan diskusi, kolaborasi, tanya jawab, dan presentasi hasil kerja. Analisis kemampuan pemecahan masalah matematis memperlihatkan bahwa sebagian besar siswa telah mampu memahami permasalahan, menyusun strategi penyelesaian, serta melaksanakan langkah-langkah penyelesaian secara tepat. Namun, sebagian siswa masih mengalami kesulitan pada tahap pengecekan kembali (looking back) karena belum terbiasa melakukan refleksi dan memverifikasi proses maupun hasil penyelesaian yang telah diperoleh. Temuan penelitian ini menunjukkan bahwa pendekatan pembelajaran mendalam mampu memberikan pengalaman belajar yang bermakna, kontekstual, dan reflektif sehingga mendukung perkembangan kemampuan pemecahan masalah matematis siswa. Dengan demikian, pendekatan pembelajaran mendalam berpotensi menjadi salah satu alternatif pembelajaran yang efektif untuk meningkatkan kemampuan pemecahan masalah matematis dalam pembelajaran matematika.